A Quantitative Liquidity Model for Banks - Schmaltz, Christian (Gabler Verlag : Imprint: Gabler Verlag, 2009)
Internal liquidity models for banks have gained considerable importance since German regulators have decided to accept them for regulatory reporting. Christian Schmaltz identifies product cash flows, funding spread, funding capacity, haircuts, and short-term interest rates as key liquidity variables. Then, he assumes specific stochastic processes for the key variables leading to a particular liquidity model. The modelling focus lies on the product cash flow that is described by a jump-diffusion process. Finally, the author applies the model to the allocation, internal pricing, and optimization of liquidity.